Urban River Bathing and Drowning: A Comprehensive Socio-Hydrological Challenge Through a Multidisciplinary Approach - Célia Maghakian; Oldrich Navratil; Nicolas Rivière; Anne Honegger (2025)
Urban rivers have emerged as valuable recreational spaces in Europe in recent years, particularly for bathing, in response to the growing need for cooling and nature-based outdoor activities in cities (Barton & Grant, 2012; Corburn, 2017). While river bathing improves urban livability and strengthens social connections, it remains largely prohibited in France, unlike in other European countries where this practice is seen as generating "social connectivity" (Wuijts, 2022; Kondolf & Pinto, 2017). This restriction has contributed to the rise of unsupervised bathing, which poses significant drowning risks (Sindall et al., 2022), especially in unregulated areas with strong currents. This research focuses on the Lyon metropolitan area (France), where accidental and intentional drownings present a critical public health concern and operational challenge for rescue teams, analyzed through a socio-hydrological lens to explore complex human-water interactions.Addressing the issues of bathing and the associated risk of drowning in urban rivers requires an interdisciplinary approach, combining geography, epidemiology, hydrology, hydraulics, and experimental methods (Maghakian, 2023). This study emphasizes the importance of focusing on the local scale, to better capture the specific dynamics of drowning risks and develop targeted prevention strategies (World Health Organization, 2017). Two main axes structure the work: (1) an analysis of biophysical, social, and spatial factors influencing drowning risks, based on a comprehensive database of incidents and a survey on both current bathing practices and residents’ projections for river bathing by 2030; (2) the development of practical solutions designed for rescue teams, supported by the study of the accuracy of eyewitness testimonies and experimental drift tests using mannequins to model body trajectories. Through an interdisciplinary focus on the complex dynamics of urban rivers at a metropolitan level, this research provides practical recommendations for both risk understanding and management, enhancing prevention strategies and rescue operations.BibliographyBarton, H., Grant, M., 2013. Urban Planning for Healthy Cities. J Urban Health 90, 129–141. https://doi.org/10.1007/s11524-011-9649-3Corburn, J., 2017. Urban Place and Health Equity: Critical Issues and Practices. International Journal of Environmental Research and Public Health 14, 117. https://doi.org/10.3390/ijerph14020117Kondolf, G.M., Pinto, P.J., 2017. The social connectivity of urban rivers. Geomorphology, Connectivity in Geomorphology from Binghamton 2016 277, 182–196. https://doi.org/10.1016/j.geomorph.2016.09.028Maghakian, C., Navratil, O., Zanot, J.-M., Rivière, N., Honegger, A., 2024. Drowning incidents in urban rivers: An underestimated issue with future challenges in need of an interdisciplinary database to characterise its epidemiology. Environmental Challenges 14, 100822. https://doi.org/10.1016/j.envc.2023.100822Sindall, R., Mecrow, T., Queiroga, A.C., Boyer, C., Koon, W., Peden, A.E., 2022. Drowning risk and climate change: a state-of-the-art review. Injury Prevention 28, 185–191. https://doi.org/10.1136/injuryprev-2021-044486Wuijts, S., Friederichs, L., Hin, J.A., Schets, F.M., Van Rijswick, H.F.M.W., Driessen, P.P.J., 2022. Governance conditions to overcome the challenges of realizing safe urban bathing water sites. International Journal of Water Resources Development 38, 554–578. https://doi.org/10.1080/07900627.2020.1755617